Intensity of 137Cs and 40K accumulation by lily-of-the-valley (Convallaria majalis L.) in Zhytomyr Polissia - Орлов, О. О.; Жуковський, О. В.; Курбет, Т. В.; Шевчук, В. В. (Forestry and Forest Melioration, 2024)
Introduction After the Chernobyl disaster, most research has focused on 137Cs, while the natural radioisotope 40К, which is considered as an analogue of 137Cs, has been studied only fragmentary. In ecosystems, potassium is known to compete with 137Сs, acting as its antagonist. This study aimed to quantify the accumulation intensity of 137Cs and 40K in the phytomass of lily-of-the-valley (Convallaria majalis L.) from contaminated soil. Materials and Methods The study was conducted in 2023 at four experimental plots (EP) in Branch «Luhyny Forestry» of the State Specialized Forest Enterprise «Forests of Ukraine». Floristic association Serratulo-Pinetum (sylvestris) (Matuszkiewich 1981) J. Matuszkiewich 1988 was presented on all experimental plots. Six subplots (1m2 each) were laid down per experimental plot, where aboveground phytomass of C. majalis was collected, and soil samples were taken to a depth of 10 cm. As an indicator of the intensity of 137Cs and 40К accumulation by phytomass, transfer factor (TF) was calculated as the ratio of radionuclide activity concentration in the phytomass (Am, Bq·kg-1) to the soil contamination density of the respective radionuclide (As, kBq·m-2). Results It was revealed that 137Cs activity concentration in soil ranged from 4109 ± 612,3 Bq·kg-1 (EP-1) tо 576 ± 50,5 Bq·kg-1 (EP-5), and 40K activity concentration in the soil varied from 69 ± 6,1 Bq·kg-1 (EP-1) tо 118 ± 7,5 Bq·kg-1 (EP-6). In C. majalis phytomass, 137Cs content ranged from 112 ± 20,2 Bq·kg-1 (EP-6, As = 61,5 ± 5,30 kBq·m-2) tо 4212 ± 31,5 Bq·kg-1 (EP-1, As = 345,1 ± 45,35 kBq·m-2). The range of 40K activity concentration in phytomass was narrower, from 667 ± 45,9 Bq·kg-1 (EP-1, As = 6,0 ± 0,74 kBq·m-2) tо 932 ± 44,8 Bq·kg-1 (EP-6, As = 9,5 ± 0,84 kBq·m-2). On almost all plots, the average 40K activity concentration in C. majalis phytomass significantly exceeded that of 137Cs. The mean TF value for 137Cs was 1,9 ± 0,41 m2·kg-1·10-3, whereas for 40K it was 106,3 ± 4,43 m2·kg-1·10-3. The statistical distribution of TF values for both radionuclides in the soil–phytomass system followed a lognormal pattern, skewed toward lower values. A statistically significant negative linear correlation (r = -0.56, p = 0.004) was observed between the soil activity concentration ratio of 137Cs/40К and the TF values of 137Cs. Conclusions 40K activity concentration in soil was significantly lower than that of 137Cs across all experimental plots. In Convallaria majalis phytomass, the trend was reversed, with 40K activity concentrations significantly exceeding those of 137Cs. The mean TF value for 137Cs in the soil–phytomass chain was essentially lower than that of 40K (1,9 ± 0,41 m2·kg-1·10-3 vs. 106,3 ± 4,43 m2·kg-1·10-3, respectively. The statistical distribution of TF values for 137Cs and 40K in the soil–phytomass chain followed a lognormal pattern, with a skew toward low values. A significant negative correlation (r = -0.56, p = 0.004) was found between soil 137Cs/40К activity concentration ratios and 137Cs TF values, indicating that increased potassium levels in soil reduce 137Cs accumulation in phytomass. 5 Figs., 3 Tables, 28 Refs.